GREEN ARCHITECTURE AND ENERGY EFFICIENCY AS A TRIGGER TO DESIGN CREATIVITY: A CASE STUDY TO PALEMBANG CITY LIBRARY - Meivirina Hanum; Chairul Murod (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2014)
Facts said that the main consumer to energy is a building; or high and big scale ones. This sector needs almost 100% of artificial energy. Dependability to this artificial energy results in environment destruction: energy’s exploitation and global warming. This conditional was triggering architects to be wiser and be more creative in designing to the energy efficiency concept.Green Architecture is one of the answers to this challenge in architecture design process. The exploration to architecture design concepts that based on energy efficiency became an alternative and also demands to professional architects this era.Palembang City Library design - which its 60-70% area is a swamp - was using stage concept to minimize the swamp piling up. Beside that, it’s choosing innovative and green material technology to fulfill the needs of lighting and circulation of library.